ACM SIGGRAPH 2016 Courses 2016
DOI: 10.1145/2897826.2927303
|View full text |Cite
|
Sign up to set email alerts
|

Vector field processing on triangle meshes

Abstract: While scalar fields on surfaces have been staples of geometry processing, the use of tangent vector fields has steadily grown in geometry processing over the last two decades: they are crucial to encoding directions and sizing on surfaces as commonly required in tasks such as texture synthesis, non-photorealistic rendering, digital grooming, and meshing. There are, however, a variety of discrete representations of tangent vector fields on triangle meshes, and each approach offers different tradeoffs among simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…A vector field refers to a function where each point in a space is assigned a vector -often, the space is a surface and the vectors are tangent to the surface. A vector field is frequently required as input in many applications including texture synthesis, nonphotorealistic rendering, anisotropic shading and fluid simulation, to control surface appearance [40]. Due to these applications in computer graphics, vector field design, or methods to create vector fields that satisfy user constraints, has been an important area of research [41], [42].…”
Section: Vector Field Designmentioning
confidence: 99%
“…A vector field refers to a function where each point in a space is assigned a vector -often, the space is a surface and the vectors are tangent to the surface. A vector field is frequently required as input in many applications including texture synthesis, nonphotorealistic rendering, anisotropic shading and fluid simulation, to control surface appearance [40]. Due to these applications in computer graphics, vector field design, or methods to create vector fields that satisfy user constraints, has been an important area of research [41], [42].…”
Section: Vector Field Designmentioning
confidence: 99%
“…Thus, the directional information is solely contained in the traceless deviatoric part . Consequently, the eigenvalues λ′ i of D encode a 2‐vector field ± λ′ i u i [dGDT15] with singularities at points where D vanishes. A common approach to 2‐tensor fields is to choose local coordinate systems (e.g.…”
Section: Representationmentioning
confidence: 99%
“…A recent course on vector field processing [dGDT15] provides an additional introduction to the topic, with a focus on the aspects of discretization (vertex vs. edge vs. face based) of vector fields.…”
Section: Introductionmentioning
confidence: 99%
“…They are used for controlling anisotropic shading of surfaces [MRMH12, RGB*14], non‐photorealistic rendering [HZ00, YCLJ12, CYZL14], texture generation [WL01, KCPS15], simulation of fluid and liquids on surfaces [AWO*14, AVW*15], surface segmentation [SBCBG11, ZZCJ14] and surface construction [IBB15, PLS*15]. For a recent surveys on direction field synthesis, design, and processing, we refer to [dGDT15, VCD*16]. Methods that use tangential vector fields and more general direction fields for surface meshing have received much attention in recent years.…”
Section: Related Workmentioning
confidence: 99%
“…We want to remark that after the submission of this paper we found that concurrently to our work the discrete Hodge–Laplace operator for piecewise constant vector fields was also introduced in [dGDT15] and a scheme for computing the eigenfields using eigenfunctions was introduced in [LMH*15], also concurrent to this work.…”
Section: Introductionmentioning
confidence: 97%